KUALITAS AIR PADA BERBAGAI PENUTUPAN LAHAN DI DAERAH ALIRAN SUNGAI BIALO - Anriana anriana; Wahyuni wahyuni; Usman Arsyad; Andang Suryana Soma (Program Studi Kehutanan Universitas Muslim Maros, 2020)
This study examined water quality from various land cover in the Bialo watershed. Water sampling was carried out at three land cover namely, primary dryland forest, scrubland and dryland agriculture. sampling was carried out four times, two before rain and two after rain. The parameters measured were temperature, TSS, turbidity, color, pH, BOD, and DO. The results of water quality parameters are temperature values of 19.0-25.2 0C, turbidity ranged from 0.3-14,4 NTU, TSS 3.47-23.0 mg/l, color 0 Pt.Co- 39 Pt.Co, pH ranges from 6.99-7.16, BOD 0.29-2.05 mg/l and DO values ranged from 6.27-8.10 mg/l. The results of the study show that water quality in the Bialo Watershed from primary forest land cover is better than shrubs and dry land farming as indicated by the value of temperature, TSS, turbidity, color and BOD were low and high DO values.